Proof of Legal Actions by Alternative Means to Written Evidence by The Defendant's Act: An Applied Comparative Analytical Study - Kawan Ismail Ibrahim; Yasin Muhammed Said (QALAAI ZANIST SCIENTIFIC JOURNAL, 2021)
Legal conducts is part of the legal facts that are the subject of proof before the courts, and originally the proof of the legal conduct need to be by written evidence, by those who protesting to what is not apparent in the first place, by presentation, or imposition, this origin is an important rule of contemporary civil evidence. The fact that the written evidence is the basis for proving legal conduct is therefore the evidence that is more consistent than its content, since it would prove a right or deny it more openly than other evidence, and for that reason. The various laws and legislations concerned with this guide and gave it a prominent position, as it is one of the guarantees to protect the rights of litigants, and thus provide judicial justice on its basis. The legislature's regulation of the legal rules governing the prosecution of legal conduct in alternative ways to the written evidence is to prove the facts establishing the rights claimed in ways that are easier than the written evidence in the absence of the latter There are multiple cases, when one of them is verified, legal action can be proven by alternative methods to the written evidence, including the case of proof by alternative methods due to the defendant’s act and refusal, written evidence without legal text.